Classification of the extreme points of ${\mathcal L}_s(^2l_{∞}^3)$ by computation - Kim, Sung Guen (Carpathian Mathematical Publications, 2022)
Let $l_{∞}^3=\mathbb{R}^3$ be endowed with the supremum norm. In [Comment. Math. 2017, 57 (1), 1-7], S.G. Kim classified the extreme points of the unit ball of ${\mathcal L}_s(^2l_{∞}^3)$ only using Mathematica 8, where ${\mathcal L}_s(^2l_{∞}^3)$ is the space of symmetric bilinear forms on $l_{∞}^3$. It seems to be interesting and meaningful to classify the extreme points of the unit ball of ${\mathcal L}_s(^2l_{∞}^3)$ without using Mathematica 8. The aim of this paper is to make such classification by mathematical calculations.